2015
DOI: 10.2174/1871520614666141130125148
|View full text |Cite
|
Sign up to set email alerts
|

Isothiouronium Salts Reduce NRAS Expression, Induce Apoptosis and Decrease Invasion of Melanoma Cells

Abstract: Melanoma is a very aggressive type of skin cancer. Mutation in BRAF and NRAS are often found in patients with this disease. Therefore, in recent years the search for new molecules that inhibit these proteins has been intensified. After many years with no new treatments for melanoma, the U.S. Food and Drug Administration (FDA) recently approved vemurafenib. However, many patients have already acquired resistance and have experienced severe side effects. Therefore, this work aims to evaluate a new set of compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, ACAT2 (Q9BWD1) was involved in diverse metabolic pathways, such as those of butanoate, glyoxylate, dicarboxylate, propanoate, tryptophan, pyruvate, and fatty acids. It has been reported that downregulation of NRAS was closely correlated with the antimetastatic effect of isothiouronium salts in melanoma cells, miR-515-5p in breast cancer cells and introduction of let-7i to mutant p53 cells . Additionally, a strong correlation was found among metastasis, ACAT2, and hydroxyl-coenzyme A dehydrogenase, alpha subunit (HADHA) downexpression and poorer prognosis on survival of clear cell renal cell carcinoma (ccRCC) …”
Section: Discussionmentioning
confidence: 99%
“…In addition, ACAT2 (Q9BWD1) was involved in diverse metabolic pathways, such as those of butanoate, glyoxylate, dicarboxylate, propanoate, tryptophan, pyruvate, and fatty acids. It has been reported that downregulation of NRAS was closely correlated with the antimetastatic effect of isothiouronium salts in melanoma cells, miR-515-5p in breast cancer cells and introduction of let-7i to mutant p53 cells . Additionally, a strong correlation was found among metastasis, ACAT2, and hydroxyl-coenzyme A dehydrogenase, alpha subunit (HADHA) downexpression and poorer prognosis on survival of clear cell renal cell carcinoma (ccRCC) …”
Section: Discussionmentioning
confidence: 99%